Analysis of Leading Economic Sectors in Bone Regency - Hendra Setiawan; Andi Jam’an; Arniati Arniati (Journal Social Society, 2026)
This research is urgent to guide evidence-based regional policy, strengthen sectoral competitiveness, anticipate structural shifts, prioritize investment, and ensure sustainable economic growth of Bone Regency amid changing national dynamics pressures. The aim of this research is to determine the leading and non-leading sectors in the economy in Bone Regency. This study employs quantitative descriptive research using secondary time-series data. Data were collected through documentation from the Central Statistics Agency (BPS) of Bone Regency for 2019–2023 GRDP at constant 2010 prices. The research was conducted from March to April 2024. Data analysis uses the Location Quotient (LQ) method to identify leading and non-leading economic sectors by comparing sectoral GRDP shares of Bone Regency with South Sulawesi Province. The results of this research show that the leading sectors in Bone Regency are four sectors, namely agriculture, forestry and fisheries, wholesale and retail trade in car and motorbike repairs, transportation and warehousing, real estate, government administration, defense and mandatory social security, and there are two non-leading sectors, namely corporate services and real estate.